2019
DOI: 10.1148/radiol.2019182071
|View full text |Cite
|
Sign up to set email alerts
|

Optoacoustic Imaging and Gray-Scale US Features of Breast Cancers: Correlation with Molecular Subtypes

Abstract: Seno Medical Instruments provided equipment and financial support for this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…Development of molecular imaging probes to target specific breast-cancer receptors (estrogen receptor and human epidermal growth factor receptor 2 [HER2]) would enhance the molecular characterization (73), allowing for better treatment with hormonal therapy and trastuzumab. In addition, optoacoustic imaging coupled with standard grayscale US has differentiated HER2-positive and triple-negative breast cancers from luminal cancers (74). This further suggests the possible capability to differentiate HER2-positive breast cancers from triple-negative cancers, which exhibits high clinical significance as a noninvasive breast-cancer characterization technique (74).…”
Section: Clinical Msot Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of molecular imaging probes to target specific breast-cancer receptors (estrogen receptor and human epidermal growth factor receptor 2 [HER2]) would enhance the molecular characterization (73), allowing for better treatment with hormonal therapy and trastuzumab. In addition, optoacoustic imaging coupled with standard grayscale US has differentiated HER2-positive and triple-negative breast cancers from luminal cancers (74). This further suggests the possible capability to differentiate HER2-positive breast cancers from triple-negative cancers, which exhibits high clinical significance as a noninvasive breast-cancer characterization technique (74).…”
Section: Clinical Msot Applicationsmentioning
confidence: 99%
“…In addition, optoacoustic imaging coupled with standard grayscale US has differentiated HER2-positive and triple-negative breast cancers from luminal cancers (74). This further suggests the possible capability to differentiate HER2-positive breast cancers from triple-negative cancers, which exhibits high clinical significance as a noninvasive breast-cancer characterization technique (74).…”
Section: Clinical Msot Applicationsmentioning
confidence: 99%
“…The four tumor subtypes, luminal A (LUMA), luminal B (LUMB), triple negative breast cancer (TNBC), and human epidermal growth factor receptor type 2 enhanced (HER2-E), and their characteristics [69][70][71][72] are presented in Table 3. Menezes et al 73 reviewed results from the Maestro trial, and Dogan et al 74 reviewed results from the Pioneer trial to investigate whether tumor subtypes could be differentiated based on PA/US features. The studies found that the internal PA features (functional characteristics such as Hb, HbO 2 , and sO 2 ) and the peripheral vasculature played an important role in this classification process, along with the US feature of sound transmission (based on tumor anatomy 75 ).…”
Section: Pa Features For Breast Imagingmentioning
confidence: 99%
“…They used PA-US features to differentiate between breast cancer molecular subtypes. Dogan et al [114] performed a detailed analysis on dual-mode PA US images of 532 IBC lesions of 519 patients from the PIONEER study. They correlated PA-US features with breast molecular subtypes.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…They also found that the same features could be useful to differentiate between LUMA and TNBC from other molecular subtypes. Dogan et al [114] performed a detailed analysis on dual mode PA US images of 532 IBC lesions of 519 patients from the PIONEER study. They reported that the means of total external PA-US feature scores, i.e., boundary zone, peripheral zone vessels for luminal (A and B) breast cancers were higher, and total internal PA-US features scores, i.e., internal vessels, internal blush, and internal hemoglobin were lower than that of the triple-negative and HER2positive breast cancers.…”
Section: Question 2: What Are the Pathophysiological Factors Behind Tmentioning
confidence: 99%